ENDOGENOUS INTOXICATION IN PATIENS WITH LIVER CIRRHOSIS - Гавриш, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Cirrhosis often accompanied by the development syndrome of endogenous intoxication, manifested increasing level of medium molecular peptides both factions on a background of a nucleotide-peptide index and increasing level of of ammonia. Inclusion in the complex treatment the patients with liver cirrhosis combined with intestinal dysbiosis medication of Lactobacillus and Bifidobacterium and Methylsiliconic acid hydrogel led to normalization of these indicators, the elimination syndrome of endogenous intoxication.